Positive impact on childrenâs quality of life under non-invasive home mechanical ventilation - PedsQL application in a monocentric cohort - Ana Moura-Figueiredo; Joana Amaral; Guiomar Oliveira; Núria Madureira; Miguel Félix; Cândida Cancelinha (Publicaciones Permanyer, 2023)
Introduction: In home mechanical ventilated (HMV) children, treatment is not based on cure, but rather on preventing morbidity and mortality and promoting their well-being. This study aimed to evaluate the different dimensions of quality of life (QoL), of HMV children/adolescents of a tertiary pediatric hospital, according to children/adolescents and caregiver's perspective, and relating it to sociodemographic and clinical characteristics. Methods: We studied families who integrated the home- ventilation program. The PedsQL™ questionnaire was answered by children/adolescents and their caregivers. Sociodemographic and clinical information was recorded. Results: 46 parents and 39 children/adolescents' questionnaires were answered. The median of the average duration of ventilatory support was 3,5y. 60,9% attend full-time school. The average of general QoL, according to parents and children/adolescents, was 61,6 and 64,0, respectively, with a strong correlation between two groups (r = 0,691). Children/adolescents showed higher scores for all dimensions of QoL. In the physical dimension a very strong correlation between groups was verified. For both groups it was found that psychosocial dimension is the best predictor of QoL. Discussion/conclusion: Parents and children/adolescents shared the same perspective about QoL, with a good correlation between answers of both groups, concluding that home ventilation is an acceptable medical strategy and has impact in QoL for both.